Sun, Earth and Sky - Lang, Kenneth R. (Springer New York : Imprint: Springer, 2006)
This Second Edition of Sun, Earth and Sky updates the popular text by providing comprehensive accounts of the most recent discoveries made by five modern solar spacecraft during the past decade. Their instruments have used sound waves to peer deep into the Sun’s inner regions and measure the temperature of its central nuclear reactor, and extended our gaze far from the visible Sun to record energetic outbursts that threaten Earth. Breakthrough observations with the underground Sudbury Neutrino Observatory are also included, which explain the new physics of ghostly neutrinos and solve the problematic mismatch between the predicted and observed amounts of solar neutrinos. This new edition of Sun, Earth and Sky also describes our recent understanding of how the Sun’s outer atmosphere is heated to a million degrees, and just where the Sun’s continuous winds come from. As humans we are more intimately linked with our life-sustaining Sun than with any other astronomical object, and the new edition therefore provides modern interpretations of ozone depletion and global warming that are related to both the Sun and to human activities. Written in a light and friendly style, this lavishly illustrated book introduces the Sun and its physics, and describes all aspects of the Sun’s interaction with us on Earth.